Set Design for Jacky - CHRISTINA SMITH (2023)
Jacky is a new Australian play by Arrernte playwright Declan Furber Gillick, commissioned as part of Melbourne Theatre Company’s Next Stage Writers Program. The play was originally programmed in the 2021 season, but was postponed due to COVID-19 restrictions. The design’s stripped back aesthetic removes naturalistic constraints to enable space as dramaturgy. Initially divided through the use of light, Jacky’s attempts to compartmentalise his dual worlds of family and work. As the relationships in the play become messy, the defined spaces become similarly blurred and overlapping, resulting in a unified stage where there is no neat resolution. By extending the auditorium around the upper rear of the stage space, the audience become aware of their complicity as spectators during the pivotal scene for the characters.